A disproportionality analysis of cardiac arrhythmia associated with bisphosphonates based on the FAERS database - Feifei Wang; Guishui Xu; Qian Wang; Xinan Wu (Scientific Reports)
Abstract The impact of bisphosphonates on cardiac arrhythmia has always been controversial. We aimed to evaluate the risk of bisphosphonates (BPs) on arrhythmia and to characterize the main features of BP-induced arrhythmia by data mining the FDA adverse event Reporting System (FAERS). From the first quarter of 2016 to the second quarter of 2022, reports for BP-related cardiac arrhythmia adverse event (AE) from FAERS database were analyzed in this study. The reporting odds ratio (ROR) and information components (IC) were used to identify disproportionate reporting of BP-related cardiac arrhythmias. We identified a total of 2377 BP-related cardiac arrhythmias cases which appeared to influence more women (61.88%) than men (28.02%), with a median age of 70 (interquartile range [IQR] 59–78) years. Compared with the full database, BPs were detected with pharmacovigilance of cardiac arrhythmias (ROR025 = 1.43, [1.39–1.47]). All studied bisphosphonates except ibandronate sodium and clodronate disodium were correlated with the reporting frequency of cardiac arrhythmia (HLGT), with ROR ranging from 1.28 with pamidronate disodium to 11.08 with etidronate disodium. The spectrum of arrhythmias induced by BPs differed among therapeutic regimens. There were significant differences in the onset time among BP regimens. Bisphosphonates use is associated with adverse cardiac arrhythmias, with the exception of ibandronate sodium and clodronate disodium. Our data support differential effects of BPs on cardiac arrhythmias.